"We're better, connected" - Sönke Graf (Empirische Erziehungswissenschaft, 2019)
How to improve science teacher effectiveness? In order to find answers to this question a first step in this study is a close observation and critical reflection on the level of science teacher training courses. During an international science teacher training course, which had been previously developed in a three-year European project (CAT4U), informal conversations of the participants were recorded and analysed allowing genuine insight in the ways that teachers exchange about profession-related content among themselves. This work is a first exploratory step into a fairly new field of professional development research, which hopes to come up with some reasonable hypotheses gained from the combination of current research literature and from deeper analyses of field data, that hopefully serves as an inspiration for teacher trainers in practice as well as for further educational research.